In Vivo Efficacy of Cefiderocol against Carbapenem-Resistant Gram-Negative Bacilli in Murine Urinary Tract Infection Models. (4th October 2017) - Matsumoto, Shuhei; Kanazawa, Sachi; Nakamura, Rio; Tsuji, Masakatsu; Sato, Takafumi; Yamano, Yoshinori
Abstract: Background: Cefiderocol (S-649266), a novel siderophore cephalosporin, shows potent activity against carbapenem-resistant Gram-negative bacilli. In the cefiderocol global surveillance study that focused on carbapenem-resistant Gram-negatives (SIDERO-CR-2014/2016), the most frequent bacterial species recovered from patients with urinary tract infection (UTI) were K. pneumonia e and P. aeruginosa . The purpose of this study was to evaluate the in vivo efficacy of cefiderocol againt carbapenem-resistant K. pneumoniae and P. aeruginosa in murine UTI models. Methods: Cefiderocol, ceftazidime/avibactam (CZA), ceftolozane/tazobactam (C/T), meropenem (MEM) and cefepime (FEP) were used as the test compounds. Four test strains of E. coli EC-14, K. pneumoniae VA-357 harboring KPC-2, P. aeruginosa SR10163 (FEP-resistant strain), and NUBL-1122 harboring IMP-1 were used. MIC was determined by broth microdilution method. As recommended by CLSI, cefiderocol was tested in iron-depleted cation-adjusted Mueller Hinton broth. ICR female mice ( n = 3–6) were infected by transurethral inoculation (ca. 2 × 10 5 CFU/mouse). Treatment was initiated 4, 10, 28, 34 hours post-infection. Viable cells in kidney tissue at 48 hours post-infection were counted. Results: Against VA-357 (KPC-2), cefiderocol and CZA had the MICs of 1 and 2 μg/mL, respectively, and they showed ≥ 3-log10 CFU from the initial therapy with 100 mg/kg treatment. These efficacy were superior to those of C/T, MEM and FEP at the same dose. Against NUBL-1122 (IMP-1), cefiderocol of 100 mg/kg significantly decreased the viable cells with ≥ 3-log10 CFU (MIC, 1 μg/mL), while CZA, C/T, MEM and FEP did not show the bactericidal efficacy (MIC, ≥32 μg/mL). All the test compounds showed dose-dependent decrease in the viable cells in kidneys against ceftazidime-susceptible and -resistant strains of EC-14 and SR10163, respectively, in a reflection of their MICs. Conclusion: Cefiderocol exhibited in vivo bactericidal efficacy against carbapenem-resistant K. pneumoniae and P. aeruginosa in the UTI models, suggesting that cefiderocol is promising antibacterial agent for the treatment of cUTI infections caused by these resistant strains. Disclosures: S. Matsumoto, SHIONOGI & CO., LTD.: Employee, Salary; S. Kanazawa, SHIONOGI & CO., LTD.: Employee, Salary; R. Nakamura, SHIONOGI & CO., LTD.: Employee, Salary; M. Tsuji, Shionogi & Co.: Employee, Salary; T. Sato, SHIONOGI & CO., LTD: Employee, Salary; Y. Yamano, SHIONOGI & CO., LTD.: Employee, Salary